Beta‐hydroxy‐beta‐methylbutyrate supplementation and skeletal muscle in healthy and muscle‐wasting conditions. Issue 4 (10th May 2017) - Holeček, Milan
Abstract: Beta‐hydroxy‐beta‐methylbutyrate (HMB) is a metabolite of the essential amino acid leucine that has been reported to have anabolic effects on protein metabolism. The aims of this article were to summarize the results of studies of the effects of HMB on skeletal muscle and to examine the evidence for the rationale to use HMB as a nutritional supplement to exert beneficial effects on muscle mass and function in various conditions of health and disease. The data presented here indicate that the beneficial effects of HMB have been well characterized in strength‐power and endurance exercise. HMB attenuates exercise‐induced muscle damage and enhances muscle hypertrophy and strength, aerobic performance, resistance to fatigue, and regenerative capacity. HMB is particularly effective in untrained individuals who are exposed to strenuous exercise and in trained individuals who are exposed to periods of high physical stress. The low effectiveness of HMB in strength‐trained athletes could be due to the suppression of the proteolysis that is induced by the adaptation to training, which may blunt the effects of HMB. Studies performed with older people have demonstrated that HMB can attenuate the development of sarcopenia in elderly subjects and that the optimal effects of HMB on muscle growth and strength occur when it is combined with exercise. Studies performed under in vitro conditions and in various animal models suggest that HMB may be effective in treatment of muscle wasting in various forms of cachexia. However, there are few clinical reports of the effects of HMB on muscle wasting in cachexia; in addition, most of these studies evaluated the therapeutic potential of combinations of various agents. Therefore, it has not been possible to determine whether HMB was effective or if there was a synergistic effect. Although most of the endogenous HMB is produced in the liver, there are no reports regarding the levels and the effects of HMB supplementation in subjects with liver disease. Several studies have suggested that anabolic effects of HMB supplementation on skeletal muscle do not occur in healthy, non‐exercising subjects. It is concluded that (i) HMB may be applied to enhance increases in the mass and strength of skeletal muscles in subjects who exercise and in the elderly and (ii) studies examining the effects of HMB administered alone are needed to obtain conclusions regarding the specific effectiveness in attenuating muscle wasting in various muscle‐wasting disorders.